Coating Hidroksiapatit Pada Logam Stainless Steel 316L Menggunakan Metode DIP Coating Dengan Variabel Temperatur Sintering Dan Komposisi Air Dalam Suspensi - Putri Arini; Ahmad Fadli; Amun Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Stainless Steel 316L is metal that can be used as a bone plate, but it has low biocompatibility. To achieve better biocompatibility with bone, Stainless Steel 316L can be coated with hydroxyapatite. Hydroxyapatite (HA) is the main inorganic phase of human bone with a composition around 65% of our bone. Dip coating techniques was used to applyhydroxyapatite into Stainless Steel 316L. Stainless Steel 316L with a size of 2x1x0,1 cm was dipped into a suspension containing HA, sago starch and water mixed with a rate of 250 rpm for 20 hours. Suspension were prepared with compositions 16 gram, 18 gram and 20 gram aquadest. And then coating HA were dried in oven at temperature 110 °C for 30 minutes.Coating HA were sintered at temperatures of 600°C, 700°C and 800 °C for 1 hour. SEM observation showed that the thickness of HA coating composition of 20 gram, 18 gram and16 gram increased in the range of 42 – 144 μm. Maximum shear strength obtained in this research was 11,78 MPa.Keywords : Coating, Dip Coating, Hydroxyapatite, Stainless Steel 316L